The Role of MicroRNAs in Diabetic Nephropathy - Hao Wu; Lili Kong; Shanshan Zhou; Wenpeng Cui; Feng Xu; Manyu Luo; Xiangqi Li; Yi Tan; Lining Miao (Journal of Diabetes Research)
Diabetic nephropathy (DN), as one of the chronic complications of diabetes, is the major cause of end-stage renal disease. However, the pathogenesis of this disease is not fully understood. In recent years, research on microRNAs (miRNAs) has become a hotspot because of their critical role in regulating posttranscriptional levels of protein-coding genes that may serve as key pathogenic factors in diseases. Several miRNAs were found to participate in the pathogenesis of DN, while others showed renal protective effects. Therefore, targeting miRNAs that are involved in DN may have a good prospect in the treatment of the disease. The aim of this review is to summarize DN-related miRNAs and provide potential targets for diagnostic strategies and therapeutic intervention.